Melatonin as a Chronobiotic and Cytoprotective Agent in Parkinson's Disease - Santiago Pérez-Lloret; Santiago Pérez-Lloret; Daniel P. Cardinali (Frontiers Media S.A., 2021)
This article discusses the role that melatonin may have in the prevention and treatment of Parkinson's disease (PD). In parkinsonian patients circulating melatonin levels are consistently disrupted and the potential therapeutic value of melatonin on sleep disorders in PD was examined in a limited number of clinical studies using 2-5 mg/day melatonin at bedtime. The low levels of melatonin MT1 and MT2 receptor density in substantia nigra and amygdala found in PD patients supported the hypothesis that the altered sleep/wake cycle seen in PD could be due to a disrupted melatonergic system. Motor symptomatology is seen in PD patients when about 75% of the dopaminergic cells in the substantia nigra pars compacta region degenerate. Nevertheless, symptoms like rapid eye movement (REM) sleep behavior disorder (RBD), hyposmia or depression may precede the onset of motor symptoms in PD for years and are index of worse prognosis. Indeed, RBD patients may evolve to an α-synucleinopathy within 10 years of RBD onset. Daily bedtime administration of 3-12 mg of melatonin has been demonstrated effective in RDB treatment and may halt neurodegeneration to PD. In studies on animal models of PD melatonin was effective to curtail symptomatology in doses that allometrically projected to humans were in the 40-100 mg/day range, rarely employed clinically. Therefore, double-blind, placebo-controlled clinical studies are urgently needed in this respect.